(untitled) (Global Journal of Human-Social Science, 2019)
Around the globe among every six people one is Indian India famously refers to as the Incredible cradle of civilization It is the home place of diversity multiculturalism integrity and peace For thousands of years Indian people have nonviolently struggled a lot for equality freedom and justice and portrayed a positive image of good human beings both nationally and supranationally On the international level India has historically maintained close and friendly relations with many Arab and Islamic countries where many Indian migrants head for in search of a living The Indian Diaspora is dominant in today s world of migration In the Gulf Arab States for example the Indian community represents the salient number of expatriate residents They have been playing pivotal roles in the development and progress of the Gulf States Yet many of them lack the fundamental human rights Their contribution is undervalued and unseen by the egoism of the Gulf native residents